Enrichment of myofibrillar proteins from beef muscle by a simple sequential method - Pighin, Darío Gabriel (2008)
A great deal of attention has been paid to the most important proteins of the myofibrillar system – myosin, actin, titin and nebulin – because of their potential role in meat processing. Several methods from different sources were reported for their isolation. However, most of them are complex, tedious and focused on the isolation of one protein at a time. In the present research, these four proteins had been co-enriched simultaneously applying a simple methodology. Myofibrillar proteins extracted from semitendinosus beef muscles were submitted to ammonium sulfate precipitation. Titin and nebulin were precipitated predominantly in the saturation range of 40–60 g/L, and so were myosin heavy chain and actin in the range of 60–100 g/L. Denaturing polyacrylamide electrophoresis and electroelution were employed for the separation and isolation of the proteins of interest from the corresponding salt fractions. Western blot procedure was applied to detect and identify precisely nebulin band. Resumen: Se ha prestado mucha atención a las proteínas más importantes del sistema miofibrilar (miosina, actina, titina y nebulina) debido a su papel potencial en el procesamiento de la carne. Se informaron varios métodos de diferentes fuentes para su aislamiento. Sin embargo, la mayoría de ellos son complejos, tediosos y se centran en el aislamiento de una proteína a la vez. En la presente investigación, estas cuatro proteínas se han co-enriquecido simultáneamente aplicando una metodología simple. Las proteínas miofibrilares extraídas de músculos semitendinosos de res se sometieron a precipitación con sulfato de amonio. La titina y la nebulina se precipitaron predominantemente en el rango de saturación de 40–60 g/L, al igual que la cadena pesada de miosina y la actina en el rango de 60–100 g/L. Se emplearon electroforesis y electroelución de poliacrilamida desnaturalizante para la separación y aislamiento de las proteínas de interés de las fracciones de sal correspondientes. Se aplicó el procedimiento de transferencia Western para detectar e identificar con precisión la banda de nebulina.